How long do I have? Observational study on communication about life expectancy with advanced cancer patients. Issue 10 (October 2017) - Henselmans, I.; Smets, E.M.A.; Han, P.K.J.; de Haes, H.C.J.C.; Laarhoven, H.W.M.van
Highlights: Oncologists never spontaneously offered prognostic information; patients took the initiative. Information was provided in different formats, most common were general time frames. Oncologists used positive framing: they emphasized the best case scenario and beneficial prognostic predictors. Oncologists stressed the indeterminacy of the estimates for the individual, yet not their precision or reliability. Abstract: Objective: To examine how communication about life expectancy is initiated in consultations about palliative chemotherapy, and what prognostic information is presented. Methods: Patients with advanced cancer (n = 41) with a median life expectancy <1 year and oncologists (n = 6) and oncologists-in-training (n = 7) meeting with them in consultations (n = 62) to discuss palliative chemotherapy were included. Verbatim transcripts of audio-recorded consultations were analyzed using MAXqda10. Results: Life expectancy was addressed in 19 of 62 of the consultations. In all cases, patients took the initiative, most often through direct questions. Estimates were provided in 12 consultations in various formats: the likelihood of experiencing a significant event, point estimates or general time scales of "months to years", often with an emphasis on the "years". The indeterminacy of estimates was consistently stressed. Also their potential inadequacy was regularly addressed, often by describing beneficial prognostic predictors for the specific patient. Oncologists did not address the reliability or precision of estimates. Conclusion: Oncologists did not initiate talk about life expectancy, they used different formats, emphasized the positive and stressed unpredictability, yet not ambiguity of estimates. Practice implications: Prognostic communication should be part of the medical curriculum. Further research should address the effect of different formats of information provision.